Aerial surveys of eiders and other waterbirds on the eastern Arctic coast of Russia - Hodges, J I; Eldridge, W D (Wildfowl, 2001)
Eiders and other waterbirds were surveyed between 1993-1995 along the eastern Arctic coast of Russia by fixed-wing aircraft to obtain baseline information on size and distribution of breeding populations. Population estimates were obtained for segments of the coast stretching from Kolyunchin Bay to the Lena River delta, a distance of 2,340 kms. The Spectacled Eider was the most abundant waterbird (146,245) with 46,276 (32%) recorded on the Indigirka River delta. Steller’s Eiders were the second most abundant waterbird (128,760) with 60% recorded from the Indigirka River delta to the Yana River delta. King Eiders numbered 55,800 and were widely distributed. Common Eiders numbered 15,515 and were restricted to the eastern survey area. Population estimates for all waterbirds observed are presented. Numbers presented are not corrected for visibility bias of birds present but not seen. This survey, the first widespread systematic survey of the region, provided new information on Eider distribution and abundance, and provided baseline population data for future monitoring.